1982
DOI: 10.1042/cs0630047
|View full text |Cite
|
Sign up to set email alerts
|

Renal Clearance of [14C]oxalate: Comparison of Constant-Infusion with Single-Injection Techniques

Abstract: 1. The renal clearance of [14C]oxalate was assessed by the constant-infusion technique and single-injection technique (plasma sampling only: one-compartment and two-compartment model; plasma and urine sampling). Healthy volunteers and patients with renal stones were studied. 2. Results with the constant-infusion techniques (with and without urine sampling) were not significantly different from each other. 3. The renal clearance of [14C]oxalate measured with the single-injection technique as compared with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 1 publication
2
8
1
Order By: Relevance
“…Especially, our serum oxalate reference values in normal adult subjects are similar to those of the accepted reference methods (radioisotopic methods) (8), and recent chromatographic (6) or enzymatic methods (3,7,9). Especially, our serum oxalate reference values in normal adult subjects are similar to those of the accepted reference methods (radioisotopic methods) (8), and recent chromatographic (6) or enzymatic methods (3,7,9).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Especially, our serum oxalate reference values in normal adult subjects are similar to those of the accepted reference methods (radioisotopic methods) (8), and recent chromatographic (6) or enzymatic methods (3,7,9). Especially, our serum oxalate reference values in normal adult subjects are similar to those of the accepted reference methods (radioisotopic methods) (8), and recent chromatographic (6) or enzymatic methods (3,7,9).…”
Section: Resultssupporting
confidence: 71%
“…This disease, characterized by increased urinary excretion of oxalate, leading to recurrent urolithiasis and nephrocalcinosis, is a rare autosomal recessive inborn error of glyoxylate metabolism due to a functional defect of a liver enzyme, alanine glyoxylate aminotransferase (1). Nevertheless, recent techniques and improvements in sample processing allowed us to obtain reliable analytical methods (3,6,7) providing normal range of serum oxalate less than 3 mol/L in good agreement with in vivo isotope dilution method, which is the accepted reference method (8). Through the years, many methods have been described for the determination of oxalate in serum.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the positive correlation found by others, between the urinary clearances of creatinine and oxalate, and a constant ratio of 2 between the clearances of oxalate arid creatinine, in individuals with normal or impaired kidney function (15,28), we were unable to identify any such relationship. However, the experimental protocols applied by those authors were largely different from ours, apart from their use of the [ 34 C]oxalate isotope dilution method.…”
Section: Discussioncontrasting
confidence: 53%
“…Earlier studies suggested that there was net tubular secretion of oxalate [7]. However, recent studies in man, using newer methods to measure plasma oxalate levels -a notoriously difficult analytical challenge -have suggested fractional excretions of less than 100%, or net tubular reabsorption, in the majority of normal subjects [4,8,9].…”
Section: Renal Handling Of Oxalatementioning
confidence: 99%